2006
DOI: 10.1128/aac.01467-05
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Macrolides and Telithromycin against Leptospirosis in a Hamster Model

Abstract: Human studies support the use of ␤-lactams and tetracyclines in the treatment of leptospirosis. Additional agents from these and other classes of antimicrobials also have in vitro activity against Leptospira species, though corroborating in vivo data are limited or lacking. We evaluated the therapeutic efficacy of azithromycin, clarithromycin, and telithromycin in a lethal hamster model of leptospirosis using Leptospira interrogans serogroup Canicola serovar Portlandvere. A range of dosages for each antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…A correlation of in vitro susceptibility data to treatment outcomes in humans is lacking, although the results of in vivo animal studies with strain 11 have correlated well with the results of our in vitro testing (7,12,13).…”
Section: Discussionmentioning
confidence: 84%
“…A correlation of in vitro susceptibility data to treatment outcomes in humans is lacking, although the results of in vivo animal studies with strain 11 have correlated well with the results of our in vitro testing (7,12,13).…”
Section: Discussionmentioning
confidence: 84%
“…A group of five hamsters was left untreated as a negative control, and a group of nine hamsters was treated with doxycycline (5 mg/kg, IP, daily) as positive control. 16 All hamsters were observed multiple times a day during the 21-day study period, and any study animal showing significant pain or distress or characteristics of a moribund state was humanely euthanized. Blood cultures were obtained from each hamster at the time of death.…”
Section: Methodsmentioning
confidence: 99%
“…Using our previously developed model, 74 female golden Syrian hamsters ( Mesocricetus auratus ) weighing 80-110 g (Harlan, Indianapolis, IN) were inoculated intraperitoneally (IP) with 0.5 mL EMJH medium containing 10 5 leptospires ( L. interrogans serovar Canicola/Portlandvere strain CA-12-029/CDC Ni 1808). [15][16][17] On study days 2-6, groups of 10 animals were treated by daily IP injection with cefazolin or cephalexin in concentrations of 5, 25, or 50 mg/kg. A group of five hamsters was left untreated as a negative control, and a group of nine hamsters was treated with doxycycline (5 mg/kg, IP, daily) as positive control.…”
Section: Methodsmentioning
confidence: 99%
“…However, antibiotics residue and the probability of multidrug resistance are concerns, which may influence the safety of patients while using the antibiotic therapy. For example, James E. Moon and Zhang W reported that nearly all animals exhibited diarrhea after some types of antibiotic therapies [12,13]. Therefore, an urgent need exists for novel therapeutic agents directed against Leptospira without severe side-effects.…”
Section: Introductionmentioning
confidence: 99%